1995
DOI: 10.1038/icb.1995.48
|View full text |Cite
|
Sign up to set email alerts
|

Cell mediated immunity in Antarctic wintering personnel; 1984–1992

Abstract: Summary Cell-mediated immune responses were studied in 12 Antarctic and sub-Antarctic wintering groups at quarterly intervals over the period 1984-1992, using the cutaneous CMI Multitest. These populations are among the most isolated on earth. While the sub-Antarctic population at Macquarie Island had levels of responsiveness and hypoergy (9%) comparable to healthy populations in temperate zones, the Antarctic Continental group showed a level of hypoergy of 36%. There was no seasonal variation in the pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Although we accomplished our goal of evaluating the effect of supplementation on vitamin D status, we could not implement a broader study in this environment at this time. The Antarctic and other isolated environments are known to affect many systems, including the immune and endocrine systems, along with cognitive and behavioral function in the central nervous system (41)(42)(43)(44)(45)(46). The lack of understanding of the interrelations between vitamin D and these other systems remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although we accomplished our goal of evaluating the effect of supplementation on vitamin D status, we could not implement a broader study in this environment at this time. The Antarctic and other isolated environments are known to affect many systems, including the immune and endocrine systems, along with cognitive and behavioral function in the central nervous system (41)(42)(43)(44)(45)(46). The lack of understanding of the interrelations between vitamin D and these other systems remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Work in the 1990s indicated that Antarctic winterers had lowered immunological responsiveness. One of the studies showed that harsh environmental conditions, combined with psychosocial, physical and other stresses associated with working and living in physical isolation during the Antarctic winter, resulted in altered immune function [16,17,25]. Tingate et al [8] (1997)reported alterations in T cell function, including depression of cell-mediated immunity and a 50% reduction in T cell proliferation to phytohemagglutinin mitogen in addition to altered cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Severe environmental stress may have immunosuppressive effects, resulting in increased risk for immune-related disorders, such as infectious diseases, allergy, cancer and autoimmune disorders. Muller et al [6] have reported diminished delayed-type hypersensitivity to recall antigens in more than 250 study subjects in Antarctica compared with control subjects stationed on Macquarie Island, which is known for its harsh winter climate, but where access to the mainland is possible. A typical monocytosis was detected and a striking reduction in the proinflammatory cytokine was noted [7].…”
Section: Introductionmentioning
confidence: 99%
“…Muller has examined the response to seven antigens in a commercial skin-test system among overwintering Antarctic personnel and personnel overwintering at an accessible subantarctic island (121,122). Among the Antarctic personnel, there was a 32% decrease in sensitivity to allergens at some point in their stay, whereas the subarctic island group showed a much smaller decrease of 9%.…”
Section: Functional/response Assaysmentioning
confidence: 99%